60.9.8 problem 1863

Internal problem ID [11862]
Book : Differential Gleichungen, E. Kamke, 3rd ed. Chelsea Pub. NY, 1948
Section : Chapter 8, system of first order odes
Problem number : 1863
Date solved : Monday, January 27, 2025 at 11:43:56 PM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x \left (t \right )+3 x \left (t \right )+4 y \left (t \right )&=0\\ \frac {d}{d t}y \left (t \right )+2 x \left (t \right )+5 y \left (t \right )&=0 \end{align*}

Solution by Maple

Time used: 0.060 (sec). Leaf size: 34

dsolve({diff(x(t),t)+3*x(t)+4*y(t)=0,diff(y(t),t)+2*x(t)+5*y(t)=0},singsol=all)
 
\begin{align*} x \left (t \right ) &= {\mathrm e}^{-t} c_{1} +c_{2} {\mathrm e}^{-7 t} \\ y \left (t \right ) &= -\frac {{\mathrm e}^{-t} c_{1}}{2}+c_{2} {\mathrm e}^{-7 t} \\ \end{align*}

Solution by Mathematica

Time used: 0.005 (sec). Leaf size: 72

DSolve[{D[x[t],t]+3*x[t]+4*y[t]==0,D[y[t],t]+2*x[t]+5*y[t]==0},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to \frac {1}{3} e^{-7 t} \left (c_1 \left (2 e^{6 t}+1\right )-2 c_2 \left (e^{6 t}-1\right )\right ) \\ y(t)\to \frac {1}{3} e^{-7 t} \left (c_2 \left (e^{6 t}+2\right )-c_1 \left (e^{6 t}-1\right )\right ) \\ \end{align*}